Natureza e cultura na poesia de Pedro Casaldáliga - Santos, Michael Jhonatan Sousa (2016)
In this work we analyze the poetics of Pedro Casaldáliga, emeritus bishop of the Prelature of São Félix do Araguaia, Mato Grosso, Brazil, aiming to understand how the aesthetic resources used by the author express themes concerning culture and nature. The study allowed us to identify, in the poems, the recurrence of images according to which, “nature is a scripture" as well as metaphoric fusions of the notions of divinity, science and nature. The processes of aspect figuration of the relationship between human beings and nature were also of vital importance for understanding the studied texts. In this context, images in which emerge the look at nature and the observation of natural spaces are great highlights. We found that the structures upon which such figures are engendered express severe criticism against the production, circulation and legitimating of scientific knowledge, as well as remarkable sensitivity in his approach to people and nature, showing a reverse logic to that of capitalism and also deep admiration for natural beauty